2013
DOI: 10.1016/j.forsciint.2013.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Combining Internet monitoring processes, packaging and isotopic analyses to determine the market structure: Example of Gamma Butyrolactone

Abstract: 5The Internet is becoming more and more popular among drug users. The use of websites and 6 forums to obtain illicit drugs and relevant information about the means of consumption is a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Both the material manufactured and distributed (illicit drugs, doping substances, counterfeited materials) and Web-based traces are needed to gain some understanding (Pazos et al, 2013). The monitoring of other 'similar' markets by using different traces scattered into databases owned by many stakeholders (for example, private companies such as credit cards issuers or pharmaceutical companies, police, customs) is another step.…”
Section: Beyond Intelligence and Policingmentioning
confidence: 99%
“…Both the material manufactured and distributed (illicit drugs, doping substances, counterfeited materials) and Web-based traces are needed to gain some understanding (Pazos et al, 2013). The monitoring of other 'similar' markets by using different traces scattered into databases owned by many stakeholders (for example, private companies such as credit cards issuers or pharmaceutical companies, police, customs) is another step.…”
Section: Beyond Intelligence and Policingmentioning
confidence: 99%
“…The precursors gammabutyrolactone -GBL -(also known as by such names as Renewtrient and Blue Nitro), and 1,4-butanediol (BDO) (also known as Serenity, Enliven, Somato Pro), are used in the chemical industry, and in some cleaning and cosmetic products. In excess of 200,000 tons of GBL is produced globally each year, principally in China, Germany, India and the USA (Pazos et al, 2013). It is rarely controlled under national legislation as it is a commonly used industrial solvent.…”
Section: Availabilitymentioning
confidence: 99%
“…Internet sites offering supply and distribution of GBL are mainly (60%) based in the Netherlands, but also Poland and the UK. Pazos et al (2013) identified 39 sites selling GBL in 2010/1. Some nail varnish remover pads and solutions contain GBL, and have become a source for recreational use (EMCDDA, 2002).…”
Section: Availabilitymentioning
confidence: 99%
“…In the Netherlands, 39 websites which offered GBL were traced between January 2010 and December 2011; 60% of all webshops operated from the Netherlands (Pazos et al, 2013) and they mainly served customers in Germany and the UK. The price of GHB varies from €2 to €8/5 ml.…”
Section: Availability Illegal Trade and Legislationmentioning
confidence: 99%